Experimental and simulation analysis on energy absorption capacity of 3D printed structure design (H) - Yodan Ngaturi (Nanyang Technological University, 2024)
Additive manufacturing is a new form of manufacturing process that builds up an object by progressively adding raw material such as plastic or metal to achieve a desired shape. 3D printing is the most common type of additive manufacturing method as it is cost-effective, simple to use and can be used to create intricate geometries. This report seeks to investigate the energy absorption capacity of a 3D printed circular tube design through simulations and experimental analysis. The circular tube will be designed in SolidWorks to create a single unit cell, which will later be combined to form a 15mm x 15mm x 15mm tubular structure. ANSYS Explicit Dynamics will be used to conduct Finite Element Analysis (FEA) simulation on the tubular structure to obtain properties such as internal energy absorption, vertical force reaction and stress to plot stress-strain, force-displacement and compression efficiency graphs. By varying the internal diameter of the circular tube unit cell, different volume fractions of the same tubular structure can be created, and they will be compared against one another to understand how volume fractions can impact the energy absorption capacity of such structures. Lastly, the circular tubular structure will be compared against previous papers to see if the applied methods verify with pre-existing results from previous studies.